The dynamics of somatic indicators of basketball players under the influence of the special exercises which are directed to the increase of stability of the vestibular analyzer - Yevhen Kharchenko (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to determine stability of the vestibular analyzer of basketball players of the team of KhSAPC by indicators of somatic displacements after the standard vestibular irritations on the Barany chair, after the introduction of the special exercises in the educational - training process, which are directed on the increase of stability of the vestibular sensor-based system. Material & Methods: the analysis of references, methods of definition of a functional condition of the vestibular analyzer on indicators of somatic displacements before and after the irritation on the Barany chair, methods of mathematical statistics. 12 boys - basketball players of the men's national team of KhSAPC took part in the researches. Results: somatic indicators of a functional condition of the vestibular analyzer of students - basketball players of the team of KhSAPC, and, their changes under the influence of rotary loadings before the pedagogical experiment are given in the article. Conclusions: the analysis of the results which were received after the experiment showed the considerable improvement of indicators, according to the testing of the motive test (4x9 m (s)), hand dynamometry of 100% of a maximum and 50% of a maximum of the right and left hands (р<0,05), both before and after a rotation. The exception was made by indicators of dynamometry of the left hand of 50% of a maximum, both before and after a rotation where changes weren't essential and statistically doubtful (р>0,05).